Job hunting online and knowledge evaluation of the employees in the world - Rimkevičiūtė, Giedrė (Technological and Economic Development of Economy, 2004)
In this article the possibilities of finding the job by net are displayed. In today's world job hunting on‐line becomes more and more popular. The majority of Internet sites that can be used for job hunting is classified in thematic categories. Brainbench is the most authoritative system of the world that values skills of employees of different fields on‐line. Brainbench, the technologies of the world knowledge assessing system tests which Lithuanian market of job search ‐supply cannot offer, are being analyzed. The conclusions about the advantages and shortcommings of Brainbench system are given about the importance and significance of Brainbench certificates in job market.Article in Lithuanian.Elektroninė darbo paieška ir darbuotojų žinių įvertinimas pasaulyjeFirst Published Online: 21 Oct 2010